Real-world efficacy of spesolimab in treating generalized pustular psoriasis flares: A case series review - Chun-Bing Chen; Chun-Wei Lu; Chuang-Wei Wang; Wen-Hung Chung (Dermatologica Sinica)
This case series review examines the efficacy of spesolimab in managing generalized pustular psoriasis (GPP) flares, including those exacerbated by coronavirus disease 2019 (COVID-19) vaccination. It focuses on treatment responses in patients with GPP, specifically emphasizing interleukin-36 receptor antagonist (IL36RN) mutations and the possible association with COVID-19 vaccination. It retrospectively reviews four patients with GPP treated with spesolimab, including two of whom experienced flares following COVID-19 vaccination. All patients demonstrated improved acute flares, as indicated by reductions in Generalized Pustular Psoriasis Physician Global Assessment scores and reduced pustulation. Two cases achieved sustained clearance with personalized dosing regimens, while one severe case required ongoing multidrug therapy despite a partial response. The occurrence of post-vaccination flares raises the possibility of a correlation between COVID-19 vaccination and GPP exacerbations. Spesolimab shows promise in treating GPP, particularly with personalized dosing. Further research into genetic predispositions and the potential link between vaccination and psoriasis flares is warranted. Overall, spesolimab emerges as a promising therapeutic option, with individualized treatment strategies necessary to optimize outcomes and better understand the interplay of genetic and environmental factors.